On the asymptotic equilibrium and asymptotic equivalence of differential equations in Banach spaces - Nguyen, The Hoan; Nguyen, Minh Man; Nguyen, Sinh Bay (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We present some conditions for the asymptotic equilibrium of nonlinear differential equations and, in particular, a linear inhomogeneous equation in Banach spaces. We also discuss analogous problems for a linear equation with unbounded operator. Some obtained results are applied to problems of asymptotic equivalence.